English vocabulary for beginning ESL learners - Yates, Jean (McGraw-Hill, 2006)
Practice Makes Perfect: English Vocabulary for Beginning ESL Learners helps you develop your vocabulary by providing practice in word-building and encouraging you to analyze new words for an ever-increasing vocabulary. Each chapter of this comprehensive book focuses on a theme, such as family or travel, so you can build your language skills in a systematic manner. As you lay the foundation for an increasing vocabulary, you are able to perfect your new words with plenty of exercises and gain the confidence to communicate well in English